2012
DOI: 10.5694/mja12.10510
|View full text |Cite
|
Sign up to set email alerts
|

CareTrack: assessing the appropriateness of health care delivery in Australia

Abstract: Although there were pockets of excellence and some aspects of care were well managed across health care providers, the consistent delivery of appropriate care needs improvement, and gaps in care should be addressed. There is a need for national agreement on clinical standards and better structuring of medical records to facilitate the delivery of more appropriate care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
310
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 362 publications
(322 citation statements)
references
References 20 publications
9
310
2
1
Order By: Relevance
“…Over the past 15 years there has been a wealth of studies from many countries that suggest that around one in ten patients admitted to hospital will have an incident, some serious, with as many as half of these thought to be preventable (Baker et al, 2004, de Vries et al, 2008, Sari et al, 2007, Vincent et al, 2001). In addition, around 40% of care is not in line with research evidence or recommended practice (Runciman et al, 2012). In the UK, the scandal surrounding appalling standards of care at Mid Staffordshire NHS Foundation Trust created much media attention.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past 15 years there has been a wealth of studies from many countries that suggest that around one in ten patients admitted to hospital will have an incident, some serious, with as many as half of these thought to be preventable (Baker et al, 2004, de Vries et al, 2008, Sari et al, 2007, Vincent et al, 2001). In addition, around 40% of care is not in line with research evidence or recommended practice (Runciman et al, 2012). In the UK, the scandal surrounding appalling standards of care at Mid Staffordshire NHS Foundation Trust created much media attention.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 This may be driven in part by inadequate implementation of clinical guidelines into practice, and that clinical practice systems inadequately support self-management or co-care for consumers. Further, for musculoskeletal health in particular, a lack of implementation research has been recently identified.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study in Australia reported that patients receive appropriate, evidence-based care, on average, only 57 % of the time [7]. Despite the proliferation of clinical guidelines, there are still barriers in translating the evidence in clinical guidelines into practice across all healthcare settings [8,9].…”
Section: Introductionmentioning
confidence: 99%